Tracing Urban Drinking Water Sources: Global State of the Art and Insights From an IAEA-Coordinated Research Project - Sánchez-Murillo, R.; Ortega, L.; Vreča, P.; Žagar, K.; Shrestha, S.; Kgotlaebonywe, C.; Esquivel-Hernández, G.; Birkel, C.; Mosquera, G.; Crespo-Sánchez, P.; Zhiña, D.; Perşoiu, A.; et al. (John Wiley and Sons, 2024)
Climate change, inter-annual precipitation variability, recurrent droughts and flash flooding, coupled with increasing water needs, are shaping the co-evolution of socioeconomic and cultural assemblages, water laws and regulations, and equitable drinking water access and allocation worldwide. Recognising the need for mitigation strategies for drinking water availability in urban areas, the Isotope Hydrology Section of the International Atomic Energy Agency (IAEA) coordinated a state-of-the-art global assessment to evaluate water sources and distribution of drinking water supply in urban centres, an initiative entitled ‘Use of Isotope Techniques for the Evaluation of Water Sources for Domestic Supply in Urban Areas (2018–2023)’. Here, we report on (a) current research trends for studying urban drinking water systems during the last two decades and (b) the development, testing and integration of new methodologies, aiming for a better assessment, mapping and management of water resources used for drinking water supply in urban settings. Selected examples of water isotope applications (Canada, USA, Costa Rica, Ecuador, Morocco, Botswana, Romania, Slovenia, India and Nepal) provide context to the insights and recommendations reported and highlight the versatility of water isotopes to underpin seasonal and temporal variations across various environmental and climate scenarios. The study revealed that urban areas depend on a large spectrum of water recharge across mountain ranges, extensive local groundwater extraction and water transfer from nearby or distant river basins. The latter is reflected in the spatial isotope snapshot variability. High-resolution monitoring (hourly and sub-hourly) isotope sampling revealed large diurnal variations in the wet tropics (Costa Rica) (up to 1.5‰ in δ18O) and more uniform diurnal variations in urban centres fed by groundwater sources (0.08‰ in δ18O) (Ljubljana, Slovenia). Similarly, while d-excess was fairly close to the global mean value (+10‰) across all urban centres (10‰–15‰), reservoir-based drinking water systems show lower values (up to ~ −20‰) (Arlington, TX, USA and Gaborone, Botswana), as a result of strong evapoconcentration processes. δ18O time series and depth-integrated sampling highlighted the influence of the catchment damping ratio in the ultimate intake water composition. By introducing new, traceable spatial and temporal tools that span from the water source to the end-user and are linked to the engineered and socio-economic structure of the water distribution system, governmental, regional or community-based water operators and practitioners could enhance drinking water treatment strategies (including more accurate surface water blending estimations) and improve urban water management and conservation plans in the light of global warming.
Keywords: Tracing; Environmental science; Environmental planning; Earth science; Hydrology (agriculture); Geology; Computer science; https://purl.org/pe-repo/ocde/ford#1.05.00